KUALITAS PENGUNGKAPAN MANAGEMENT DISCUSSION AND ANALYSIS (MD&A) PERUSAHAAN FORTUNE 45 DENGAN MODEL WEBB - Muhammad Reza (LPPM Institut Pendidikan Nusantara Global, 2023)
This journal aims to directly evaluate the Quality of Management Discussion and Analysis (MD&A) disclosures in the TOP 45 Fortune Companies with the Webb model.This research was conducted at the TOP 45 companies in Fortune with the MD&A Theory Case Study Method approach using the Lori Holder Webb model.This paper provides a more intensive tool for evaluating the qualitative disclosures contained in the MD&A than is currently available to the public. This tool generates a disclosure measure that can be used in empirical or experimental research for further research, or by those wishing to objectively compare disclosure across managers, across firms, or across time.The novelty in this study is how MD&A conducts Content Analysis on the Quality of Disclosure Management Discussion & Analysis of Fortune TOP 45 Companies where in previous research the MD&A Report was hampered by the lack of empirical tools to enable disclosure analysis of disclosure quality.